2019
DOI: 10.1177/0022034519885644
|View full text |Cite
|
Sign up to set email alerts
|

Critical Issues in Dental and Medical Management of Obstructive Sleep Apnea

Abstract: This critical review focuses on obstructive sleep apnea (OSA) and its management from a dental medicine perspective. OSA is characterized by ≥10-s cessation of breathing (apnea) or reduction in airflow (hypopnea) ≥5 times per hour with a drop in oxygen and/or rise in carbon dioxide. It can be associated with sleepiness and fatigue, impaired mood and cognition, cardiometabolic complications, and risk for transportation and work accidents. Although sleep apnea is diagnosed by a sleep physician, its management is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 94 publications
0
35
0
1
Order By: Relevance
“…In fact, it appears that phenotyping OSA patients according to pathophysiologic risk factors or traits (eg, craniofacial morphology, arousal threshold, loop gain, muscle responsiveness) could help to capture OSA's heterogeneity. [23][24][25][26] RDI is another index that accounts for RERAs besides apnea/hypopnea episodes, consequently being more "inclusive" when compared with the classical AHI. While RERAs can impact sleep quality and have predictive value in cardiovascular complications according to some studies, 27 evidence from a middle-aged populationbased cohort study in Europe indicated a lack of association with negative clinical outcomes (eg, daytime sleepiness, hypertension, diabetes, or metabolic syndrome).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it appears that phenotyping OSA patients according to pathophysiologic risk factors or traits (eg, craniofacial morphology, arousal threshold, loop gain, muscle responsiveness) could help to capture OSA's heterogeneity. [23][24][25][26] RDI is another index that accounts for RERAs besides apnea/hypopnea episodes, consequently being more "inclusive" when compared with the classical AHI. While RERAs can impact sleep quality and have predictive value in cardiovascular complications according to some studies, 27 evidence from a middle-aged populationbased cohort study in Europe indicated a lack of association with negative clinical outcomes (eg, daytime sleepiness, hypertension, diabetes, or metabolic syndrome).…”
Section: Discussionmentioning
confidence: 99%
“…retrognathia), physiological breathing activity and responsiveness (e.g. low to high loop gain, arousal threshold, oropharyngeal muscle tone) (Basoglu & Tasbakan, 2018; Carberry et al., 2018; Eckert & Malhotra, 2008; Lavigne et al., 2020; Won et al., 2020). The clustering of phenotypes can contribute to define endotypes, a subtype of a condition implying distinct pathophysiological mechanisms.…”
Section: Screening and Diagnosis Tools Or Devices Used For Osa And Sbmentioning
confidence: 99%
“…The importance of investigating phenotypes and endotypes is largely related to achieving a high level of precision medicine in the management of sleep disorders (Light et al., 2019; Malhotra et al., 2020; Pepin et al., 2018). An example of the latter can be observed in OSA, where individuals presenting certain endotypes may obtain more benefits from specific management strategies (Lavigne et al., 2020). For instance, individuals with OSA that present a lower loop gain, higher arousal threshold, moderate pharyngeal collapsibility, and weaker muscle compensation showed a better response (in respect of the AHI OSA metric) to oral appliance therapy, which was independent of body mass index and neck circumference (Bamagoos et al., 2019).…”
Section: Screening and Diagnosis Tools Or Devices Used For Osa And Sbmentioning
confidence: 99%
“…Nevertheless, the accepted gold standard for vertical dimension in OA treatment is to keep the vertical dimension as low as possible. Hence, the need for individualised mandibular advancement and vertical dimension of OA in order to optimise comfort and treatment efficacy seems obvious, and would be in accordance with recent consensus within the field of dental sleep medicine 20 …”
Section: Introductionmentioning
confidence: 54%